The Involvement as a Trait of the Organizational Culture in Lithuanian General Education Schools - Starkute, Jovita (Pedagogika, 2023)
The aim of the article is to determine the expression of involvement as a trait of organizational culture and its constituent indicators (empowerment, team orientation and capability development) in Lithuanian general education schools. The participants were a total of 1817 teachers, school heads and deputies, administrative, and other workers. Denison Organizational Culture Survey was used as a measure of the involvement trait as a component of organizational culture.